Effect of phase transition on the piezoelectric properties of scandium-alloyed gallium nitride - Hirata, Kenji; Ikemoto, Yu; Uehara, Masato; Yamada, Hiroshi; Anggraini, Sri Ayu; Akiyama, Morito (Journal of applied physics, 2024)
In this study, the piezoelectric properties of scandium-alloyed gallium nitride (ScGaN), which is expected to be applied to microelectromechanical systems devices, are evaluated by first-principles calculations. The piezoelectric constant (d33) of GaN is found to increase by up to approximately 30 times upon the addition of 62.5 mol. % of Sc. The piezoelectric stress constant (e33) increases and the elastic constant (C33) decreases with increasing Sc content of ScGaN, driving the rise of d33. The improved piezoelectric properties of ScGaN compared with those of GaN are largely attributed to elastic softening, which is thought to be related to the transition from a wurtzite to hexagonal boron nitride (h-BN) structure driven by the change in bonding states between atoms caused by the addition of Sc to GaN. The crystal orbital Hamilton population analysis suggests that addition of Sc to GaN results in the combination of weaker Sc–N and Ga–N bonding, which makes the crystal structure unstable. This weakened bonding is thought to be the main cause of the destabilization of the wurtzite structure and transition to the h-BN structure of ScGaN. The elastic softening associated with this structural transition leads to the dramatic improvement in piezoelectric properties.